Short-distance dispersal of Hypothenemus hampei (Ferrari) females (Coleoptera: Curculionidae: Scolytidae) during the coffee tree fruiting period. Issue 5 (23rd November 2017) - Román-Ruiz, A.K.; Ribeyre, F.; Rojas, J.C.; Cruz-López, L.; Barrera, J.F.; Dufour, B.P.
Abstract: The coffee berry borer (CBB), Hypothenemus hampei (Ferrari), is a multivoltine species closely associated with coffee crops worldwide, causing severe damage to the bean. In Mexico, as in all tropical regions, CBB survives during the inter-harvest period in residual berries on the ground or in dry berries remaining on the branches, and then disperses in search of the first suitable berries. In this study, we investigated how CBB dispersed from the first infested nodes during the fruiting period of Coffea canephora Pierre, which provides a favourable trophic level for this insect. Forty-five branches equally distributed in 15 coffee trees, with one infested node and four uninfested nodes, were selected. The branches were subjected to three treatments over nine weeks: 1) glue between nodes with full protection, 2) glue between nodes without protection, and 3) no glue and no protection. In addition, 45 CBB-free branches were selected and subjected to the same three treatments. CBB colonization can occur in three ways: 1) from an infested node to an uninfested node on the same branch, 2) from infested berries to uninfested berries within the nodes, 3) from branches to other branches. We also found that CBB dispersal between nodes of the same branches never occurred by walking but by flying. Thus, in this context of coffee berry development and ripening, and unlike the phenological situation of the inter-harvest period, CBB continuously travels very short distances, thus limiting its control.